Sigma Iota Epsilon: The Academy's Student Division: Opportunity and Dilemma for the Management Professor - Bernthal, Wilmar F. (Academy of Management Journal, 1969)
The article reports on college students' power within their school and their ability to impact professors and the administration. Most professors typically have little to gain from undergraduate st...